KEGIATAN KULIAH KERJA NYATA (KKN) NON REGULER DI KELURAHAN SUNGGAL - Novi Lestari; Rahmadi Ali; Zulkifli Hasibuan (JURNAL PENGABDIAN MANDIRI, 2025)
The industrial revolution 4.0 brought about major changes in the era. These changes target various fields, such as economics and education. This requires people to be ready for all forms of competition. Sunggal Village is one of the Villages in Medan Sunggal District, North Sumatra Province. In this Village, there are many MSME actors. The large number of MSME actors in Sunggal Village certainly has an impact on tight competition. MSME actors are required to be able to maximize all technological advances in order to reach consumers. Departing from these findings, socialization was carried out to the Sunggal Village community about the importance of packaging, logos, and online product marketing in order to increase sales. In addition to carrying out socialization activities to MSME actors, maghrib recitation activities were also carried out in order to increase faith and piety to God Almighty, so that people can stay away from things that can harm themselves and their families in the midst of the development of the era